Penerapan Kegiatan Keagamaan melalui Khataman Qur’an di Masjid Istiqomah Griyo Mapan Sentosa Kecamatan Waru Kabupaten Sidoarjo sebagai Bentuk Pengabdian Kepada Masyarakat oleh Mahasiswa Universitas Sunan Giri Surabaya - Alfiyatur Rizkiyah; Ana Arifiana; Eli Masnawati; Eli Retnowati; Nelud Darajaatul Aliyah; Muhammad Yusron Maulana El-Yunusi; Didit Darmawan; Jahroni Jahroni; Ikhwanuddin Ikhwanuddin (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Real Work Lecture (KKN) activities are the role of students in implementing the khataman qur'an form of community service. The Real Work Lecture (KKN) of Sunan Giri Surabaya University group nineteen was held at the Griyo Mapan Sentosa Mosque Foundation, Waru District, Sidoarjo Regency. The Sunan Giri Surabaya University KKN team took an educational work program related to religion at the Griyo Mapan Sentosa Mosque Foundation. Religious knowledge must be fostered from a young age, activities in this religious field are carried out and will always exist in the lives of local people in the Griyo Mapan Sentosa Mosque Foundation area, Waru District, Sidoarjo Regency. This study uses qualitative methods and uses observation techniques and data collection by documenting activities that have been carried out. This program can be carried out well because students are able to establish good relationships with Griyo Mapan Sentosa residents and empower themselves.